Socioeconomic Position and Low Birth Weight: Evaluating Multiple and Alternative Measures Across Race in Michigan - Cedric A. L. Taylor; Dilshani Sarathchandra (Social Sciences, 2014)
In health research, socioeconomic position (SEP) is used to measure the context of social inequality. Studies on low birth weight (LBW) that attempt to capture social inequality have generally used single measures of SEP or have employed conventional SEP measures, such as income and education, without regard to how other indicators could influence findings. This study investigates the association between SEP and LBW across blacks and whites using multiple and alternative indicators of SEP. We use a stratified random sample of 13,513 postpartum mothers, obtained from the Michigan Pregnancy Risk Assessment Monitoring System (2000–2006), and evaluate four SEP measures across race: maternal education, Medicaid before pregnancy, Women, Infants and Children (WIC) enrollment during pregnancy and paternal acknowledgment. Results indicate that associations between SEP and LBW vary depending on the SEP measure used and the racial subpopulation under consideration. To explain and reduce social inequalities in LBW, a more differentiated approach that does not assume equivalence among SEP measures and across racial/ethnic groups should be employed.